The Source Antinomy of the Mystery of the Trinity as the Foundation and Hermeneutical Key of Christian Apophaticism in the View of Vladimir N. Lossky - Płóciennik, Michał (Verbum Vitae, 2023)
For some time now, there has been a definite revival of interest in apophatic theology within religious thinking as well as at its antipodes. It often takes the form of criticism of religion, including Christian Revelation, and thus the theology based on it. From a Christian perspective, this provides an invitation to reflect on the rich heritage of apophaticism and to show its specificity as a consequence of what constitutes the specificum christianorum, i.e. the Trinitatis mystery. Important clues in this regard can be found in the thought of Vladimir N. Lossky, a prominent 20th century Orthodox theologian, a radical defender of the specific apophatic nature of Christianity and a theologian faithful to Trinitarian orthodoxy. Looking at the most important issues related to the Trinitarian dogma, we will point out that in the Russian’s view, the Trinitarian antinomy is the source and foundation of Christian apophaticism and its hermeneutics. This conclusion will be based on revealing the Trinitarian antinomy as what is primordial, unconditioned by nothing, non-derivable from anything and therefore as a purely religious given and truth par excellence, accessible to man through Its free Revelation, which It also infinitely transcends.